2018
DOI: 10.1111/nph.15087
|View full text |Cite
|
Sign up to set email alerts
|

GIGANTEA‐like genes control seasonal growth cessation in Populus

Abstract: Summary Survival of trees growing in temperate zones requires cycling between active growth and dormancy. This involves growth cessation in the autumn triggered by a photoperiod shorter than the critical day length. Variations in GIGANTEA (GI)‐like genes have been associated with phenology in a range of different tree species, but characterization of the functions of these genes in the process is still lacking. We describe the identification of the Populus orthologs of GI and their critical role in short‐day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
74
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(80 citation statements)
references
References 68 publications
6
74
0
Order By: Relevance
“…It is also involved in numerous physiological processes, mediating rhythmic, phytochrome B signalling, carbohydrate metabolism and cold stress response [55]. Ding et al have described the identification of the Populus (poplar) orthologs of GI and their critical role in short-day-induced growth cessation and concluded that GI controls seasonal growth cessation in Populus [56]. In our study, GI may have played an important role in the photoperiodic control of growth cessation in E. ulmoides.…”
Section: Candidate Genes For Qtlssupporting
confidence: 54%
“…It is also involved in numerous physiological processes, mediating rhythmic, phytochrome B signalling, carbohydrate metabolism and cold stress response [55]. Ding et al have described the identification of the Populus (poplar) orthologs of GI and their critical role in short-day-induced growth cessation and concluded that GI controls seasonal growth cessation in Populus [56]. In our study, GI may have played an important role in the photoperiodic control of growth cessation in E. ulmoides.…”
Section: Candidate Genes For Qtlssupporting
confidence: 54%
“…At the molecular level, there is evidence of cooption or cross talk between Arabidopsis flowering/seed dormancy pathways and the regulation of bud set in Populus, as well as in other plant species (25)(26)(27)(28). Such shared pathways revealed the importance of the phytohormone abscisic acid (ABA) (29,30) as well as components of the CONSTANS/FLOWERING LOCUS T (FT) regulatory module (25,31,32) and GIGANTEA (GI)-like genes (33). Recent studies described a key component of bud break in hybrid aspen: the transcription factor SHORT VEGETATIVE PHASE-LIKE (SVL), closely related to Arabidopsis floral repressor SHORT VEGETATIVE PHASE and its downstream target TCP18, a tree homolog of a branching regulator in Arabidopsis (34).…”
Section: Significancementioning
confidence: 99%
“…It plays a role in control of circadian rhythm in Arabidopsis 31 . Furthermore it coordinates both photoperiod-mediated and independent flowering 32,33 , growth cessation 34 , carbohydrate metabolism 35 , salt tolerance 36 and cold stress response 37 . GI also affects hypocotyl growth in Arabidopsis 38,39 , and this function is related to gibberellin signaling, as SPINDLY (SPY) protein, a negative regulator of gibberellin signaling in Arabidopsis and an inhibitor of hypocotyl elongation, interacts with GI protein 39 .…”
mentioning
confidence: 99%